Effect of polyvinylpolypyrrolidone and membrane filter sterilization on Philippine coconut water - Diaz, Lou Marvin Hermosa; Francisco, Ma. Leonora dL. (Quezon City UP College of Home Economics, 2012)
A cold sterilization process model was performed in extending the shelf-life of coconut water without compromising its quality. Effects on physico-chemical, sensory, microbiological, turbidity, total phenolic content, and polyphenol oxidase (PPO) activity of coconut water were determined on storage days 0, 5, and 12. Untreated sample (A) and three levels of PVPP with membrane filter sterilization were studied: 5g/hL (B), 10g/hL (C), 20g/hL (D). Results showed that pH and %TA of the samples were not affected by the treatments employed: total soluble solids and turbidity decreased as level of PVPP increased; total phenolic content decreased in Days 0 and 5 as PVPP levels increased; and PPO activity diminished more rapidly for 'B', 'C', and 'D' than 'A'. The results indicate the efficacy of PVPP in adsorbing particulates including polyphenols which when oxidized can be detrimental to coconut water quality. Aroma acceptance for 'A' were significantly lower (P < 0.05) than 'B', 'C', and 'D' in Day 5; aroma intensity across all treatments were rated "very weak" to "weak" and off-odor intensity "none" to "very weak" with no significant difference among all treatments. Ratings were mainly due to the muted intensity of aroma brought by the cold serving temperature (0-4°C). Aerobic plate count for all samples was below the FAO specification <5000 total microbiological count per mL while most had <100 cfu/mL yeast and mold count with some exceptions that were above the FDA specification of <10 cfu/mL. Treatment 'C' (10g/hL PVPP with membrane filter sterilization) proved to be optimum level of PVPP addition.
Thesis (B.S. Food Technology)--University of the Philippines.
Keywords: Coconut water